Geriatric neurology - Nair, Anil (Anil Kadoor), 1970-; Sabbagh, Marwan Noel (Wiley Blackwell, 2014)
Aging affects neurological function leading to neurological disease As society grows older, so do the neurological problems associated with aging. These can be new neurological deficits due to the aging process itself, or the effect of aging on already existing neurological conditions. Neurologists will spend increasing amounts of time managing patients with age-related neurological complications. Geriatric Neurology brings together the wisdom of world-leading experts. They have crafted a new textbook to define this emerging subspecialty from basic science through.